Social Conflict Reflected by Main Characters in the ‎Movie of Harry Potter & Sorcerer’s Stone - Arianto, Nurlaila; Abdullah; Iskandar (IAIN KENDARI, 2024)
This study aims to analyze the types of social conflict found in the film Harry Potter and the Sorcerer's ‎Stone (2001), especially those that occur in main characters, Harry Potter, Ronald Weasley, and ‎Hermione Granger. In addition, this study seeks to outline the reasons why these conflicts arise and ‎show the results or effects that the main character experiences as a result of conflict, whether they are ‎favorable or unfavorable. The descriptive qualitative approach used in this study aims to explain how ‎the author's upbringing and the literature they created are related. Both primary and secondary data were ‎used as data sources for this research. The method of observing and taking notes was used in this ‎research as a data collection strategy. After analyzing the types, consequences, and consequences or ‎impacts of social conflict in Harry Potter and the Sorcerer's Stone (2001), the researcher concludes the ‎analysis into three findings: first, there have been found five types of social conflict, namely individual ‎conflicts with individuals, conflict between races, conflicts between social classes, conflicts between ‎social groups, and individual internal conflicts. Second, there are three main causes that give rise to ‎conflicts in this film, namely differences between individuals, differences in interests, and cultural ‎differences. Third, for negative impacts of social conflict, they are social conflicts can also lead to ‎hostility in society, conflict may occur is the fall of victims. For positive impacts of social conflict, they ‎are conflict can help revive old norms, a way to reduce dependence between individuals and groups, ‎increase solidarity, and create a new compromise‎